The value of lung ultrasound score combined with echocardiography in assessing right heart function in patients undergoing maintenance hemodialysis and experiencing pulmonary hypertension - Ying Xia; Xin Liu (BMC Cardiovascular Disorders)
Abstract Aims This study explores the clinical application of lung ultrasound scoring(LUS) combined with echocardiography in assessing right heart function in patients undergoing maintenance hemodialysis(MHD) and those with elevated pulmonary artery systolic pressure(PASP), as well as the correlation between LUS and right ventricular(RV) function. Methods Eighty five patients who underwent MHD combined with elevated PASP, at the First Central Hospital of Baoding City were selected. Divided into three groups based on PASP, and perform echocardiography and lung ultrasound examinations. Compare the right heart function parameters and LUS among the three groups. Using Pearson correlation analysis to examine the relationship between LUS and right heart function parameters. Perform multivariate logistic regression analysis to identify predictive factors for RV systolic dysfunction. A receiver operating characteristic (ROC) curve and calculate the area under the curve(AUC) to compare the diagnostic efficacy of various parameters. Results Patients undergoing MHD exhibited varying degrees of reduced left ventricular (LV) and RV systolic function. Correlation analysis revealed that Tricuspid annular plane systolic excursion (TAPSE), Fractional area change (FAC), and Tricuspid annular peak systolic velocity(S') were negatively correlated with LUS(r = -0.81, -0.86, -0.69), while Right ventricular free wall longitudinal strain(RVFWLS) was positively correlated with LUS (r = 0.85, P < 0.05). The ROC curve indicated that the combination of LUS and RVFWLS had the highest area under the curve (AUC = 0.963), followed by the combination of LUS and TAPSE (AUC = 0.847), LUS and FAC(AUC = 0.937), and LUS combined with S'(AUC = 0.940). All combinations demonstrated higher AUC values than the individual indicators. Conclusions Patients with MHD combined with elevated PASP, the RV function parameters are associated with LUS, which may serve as a valuable reference indicator for assessing RV function. The use of LUS to evaluate right heart function in these patients, alongside traditional two-dimensional parameters, holds significant clinical value.